Socio-economic determinants of willingness to pay for safe and sustainable water supply in coastal urban areas - Vivian Alvianti (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: In many urban developing countries, the main obstacle to expanding and providing piped water supply is the cost to consumers. The coastal area of Bandar Lampung City is a slum seaside area that has a poor piped clean water supply system that requires improvements to various aspects of the system. So it is important to estimate the Willingness to Pay of the community to improve the quality of sustainable clean water which is determined by their socio-economic characteristics. The purpose of this study is to identify the amount of willingness of the residents of the coastal area of Bandar Lampung City to improve the quality of clean water. Methods: The analytical method used is descriptive quantitative with Willingness calculations and binary logistic regression. This study will take a sample of 100 families living in Teluk Betung Selatan District, Teluk Betung Timur, Bumi Waras District, and Panjang District as areas that are in direct contact with the coastal area of Bandar Lampung City. Finding: The results of this study indicate that the average willingness of PDAM customers to pay to improve the quality of clean water is IDR 99,000 with gender and number of family members. Meanwhile, for residents who are prospective PDAM customers, the average willingness to pay is IDR 130,283 and the influencing factors are age and type of work. Conclusion: It can be seen that the willingness of the community to improve the quality of drinking water is quite high. The results of this study are as a reference for relevant stakeholders to improve the quality of clean water due to the high willingness of the community to pay in the coastal area of Bandar Lampung City. Novelty/Originality of this article:The novelty of this study lies in its contextual analysis of community willingness to pay for clean water improvement in coastal urban slum areas, an aspect rarely examined in previous research on water economics in Indonesia.